The Protective Role of Certain Antioxidants (Vitamins C, E and Omega-3) Against Aluminum Chloride Induced Histological Changes in the Liver and Kidney of Female Albino Rats (Rattus Rattus Norvegicus) - Gorgees, Najem S.; Al. Habbib, Omar A.M.; Hussein, Reyzan A. (Science Journal of University of Zakho, 2013)
The present study was undertaken to evaluate the protective effect of certain antioxidants such as Vitamins C, E and Omega-3 oil on Aluminum induced histological changes in the liver and kidney of the female albino rats. Sixty four female adult rats were divided randomly into eight groups two of them control: (control 1) without AlCl3 /Kg body weight (b.w.); (control 2) supplied orally with 0.2 ml/rat oil and six groups treated as follow: AlCl3 (60 mg/kg b. w.) ; AlCl3 (60 mg/kg b. w.) plus 0.2ml/rat acetic acid (0.5%); AlCl3 (60 mg/kg b. w.) plus Vit.C (50 mg/kg); AlCl3 (60 mg/kg b. w.) plus Vit.E (100 mg/kg); AlCl3 (60 mg/kg b. w.) plus 0.2 ml/rat Omega-3 (5% ) and AlCl3 (60 mg/kg b. w.) plus Vit.C (50 mg/kg) plus Vit.E (100 mg/kg) plus 0.2ml/rat 5 % Omega-3 ) respectively. Rats were orally administered their respective doses every other day for 35 days. At the end of the experiments, livers and kidneys samples were fixed in Bouin’s fluid and processed for histological examination.Histological examination of liver taken from rats treated with aluminum chloride in the presence or absence of acetic acid showed several abnormalities in the structure of liver histology such as dilatation of blood sinusoid, degeneration of hepatocytes, vacuolated hepatocytes, necrosis, apoptosis, infiltration of lymphocytes, and steatosis. Furthermore, Kidneys taken from rats treated with aluminum chloride also, showed some abnormalities in kidney histology such as inflammation, degeneration of kidney tubules cells and hemorrhage. The presence of antioxidants (Vitamins C, E and omega-3 oil) along with aluminum chloride relatively diminished the toxic effect of aluminum on both liver and kidney and tended to protect them as indicated by more or less normal histological structure of liver and kidney.